Junior High School Science Teachers' Perceptions of Science Scientists, Science Subjects, NOS, and NOSI - Fitratunisyah; PRELIA DWI AMANAH; Thufail Mujaddid Al-Qoyyim; Eka Muliati; Muhammad Tantawi Jauhari; A Wahab Jufri (Postgraduate Program, University of Mataram, 2025)
Scientists play a crucial role in the advancement of science and technology; however, public perceptions of them are still influenced by various stereotypes and limited understanding. Science teachers, as educators who shape students' perceptions of scientists, hold views that can influence how science is taught and understood in schools. This study aims to analyze science teachers' perceptions of scientists, covering aspects such as the image of scientists, trust in the scientific method, scientists' relationship with society and education, their relevance to religious and cultural values, and the attractiveness of the scientist profession. The study employed a survey method involving 61 science teachers from various schools in Indonesia. The findings indicate that while most respondents have high confidence in scientists and the scientific method, there remains a gap in the representation of contemporary scientists in education and media. Additionally, scientists are still perceived as having limited involvement in formal education and public communication. Although the scientist profession is regarded as appealing, challenges such as gender stereotypes and the exclusivity of science continue to be barriers. Therefore, more inclusive strategies in science education and communication are needed to strengthen the role of scientists in society.